2020
DOI: 10.1111/lam.13254
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteria in bovine ovarian follicular fluid

Abstract: Significance and Impact of the Study: The results of the present study show that ovarian follicular fluid is not sterile in bovines. The presence of Staphylococcus aureus in follicular fluid may partly explain the occurrence of infertility in some dairy cows. AbstractThe aim of this study was to examine the sterility of follicular fluid in large ovarian follicles in dairy cows. In all, 17 samples of paired follicular fluids and uterine contents collected from post-slaughtered dairy cows were cultured to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…and Staphylococcus spp. [8,11] could be isolated from human follicular fluid samples under different media and atmospheric conditions; Staphylococcus aureus was identified in follicular fluid samples collected from post-slaughter dairy cows [14]. Our results were partly in line with the previous studies on bacteria in follicular fluid collected from humans and animals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…and Staphylococcus spp. [8,11] could be isolated from human follicular fluid samples under different media and atmospheric conditions; Staphylococcus aureus was identified in follicular fluid samples collected from post-slaughter dairy cows [14]. Our results were partly in line with the previous studies on bacteria in follicular fluid collected from humans and animals.…”
Section: Discussionsupporting
confidence: 90%
“…Staphylococcus infections may occur and influence reproductive functions and can induce endometritis, leading to infertility [48]. In addition, the presence of S. aureus in follicular fluid might partly explain the occurrence of infertility in some dairy cows [14]. Recently, Streptococcus agalactiae was identified as a taxon of placental origin [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms have been identified both in the upper and lower tracts. The upper tract was originally thought to be sterile, but promising research has indicated the existence of microorganisms in the follicle, fallopian tubes, uterus, and placenta [3] , [7] , [47] , [48] . The lower reproductive tract shows high diversity and abundance of microbiomes [7] , [49] .…”
Section: Female Reproductive Microbiomementioning
confidence: 99%
“…The ovarian follicles can be colonized, and several studies have shown the presence of microorganisms in follicular fluid, not only in humans but also in bovines and swine, among other animals [48] , [50] . Follicular fluid plays important roles in ovarian physiology, including in steroidogenesis, follicle growth, ovulation, oocyte maturation, and oviduct transport.…”
Section: Female Reproductive Microbiomementioning
confidence: 99%